2021
DOI: 10.1126/scitranslmed.abd3438
|View full text |Cite
|
Sign up to set email alerts
|

Engineering adeno-associated viral vectors to evade innate immune and inflammatory responses

Abstract: Nucleic acids are used in many therapeutic modalities, including gene therapy, but their ability to trigger host immune responses in vivo can lead to decreased safety and efficacy. In the case of adeno-associated viral (AAV) vectors, studies have shown that the genome of the vector activates Toll-like receptor 9 (TLR9), a pattern recognition receptor that senses foreign DNA. Here, we engineered AAV vectors to be intrinsically less immunogenic by incorporating short DNA oligonucleotides that antagonize TLR9 act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(86 citation statements)
references
References 50 publications
1
85
0
Order By: Relevance
“…In case of editing the promoter, one would have to empirically determine which sequences can be changed and what to change them to without altering promoter strength or specificity. An alternative approach to eliminate TLR9 signaling is to include TLR9 inhibitory DNA sequences in the vector construct, as recently been shown by Chan et al (54). However, it should be pointed out that even TLR9 deficient mice do not show complete abolishment of CD8 + T cell responses, as our current and published studies have shown (7)(8)(9).…”
Section: Discussionmentioning
confidence: 62%
“…In case of editing the promoter, one would have to empirically determine which sequences can be changed and what to change them to without altering promoter strength or specificity. An alternative approach to eliminate TLR9 signaling is to include TLR9 inhibitory DNA sequences in the vector construct, as recently been shown by Chan et al (54). However, it should be pointed out that even TLR9 deficient mice do not show complete abolishment of CD8 + T cell responses, as our current and published studies have shown (7)(8)(9).…”
Section: Discussionmentioning
confidence: 62%
“…If achievable, methylation of CpG motifs to ‘humanize’ this epigenic attribute is predicted to reduce TLR9 activation. Another approach is the incorporation of TLR9 inhibitory nucleotides sequences into the AAV expression cassette ( 60 ).…”
Section: Cellular Immune Responses To Aavmentioning
confidence: 99%
“…ML-powered capsid design and engineering will transform the landscape of GT delivery modalities, however non-capsid improvements are also relevant from an immunological perspective and can also increase therapeutic effectiveness. Reducing the activation of innate immunity by engineering the vector genome (66,67), co-administration with targeted immune-modulators to induce tolerance toward the vector (68) or depletion of pre-existing anti-capsid antibodies (69) should work in synergy with engineered capsids to pave a path for repeat vector administration, while further increasing the safety and tolerability of next generation GTs.…”
Section: Future Directionsmentioning
confidence: 99%